Returns to apprenticeship training in Austria: evidence from failed firms - Josef Fersterer; Jörn-Steffen Pischke; Rudolf Winter-Ebmer (Institute for the Study of Labor (IZA), 2007)
Little is known about the payoffs to apprenticeship training in the German speaking countries for the participants. There is a lot of heterogeneity in the types of apprenticeships offered, and there might be an important element of selection in who obtains an apprenticeship, and what type. To overcome the resulting ability bias we estimate returns to apprenticeship for apprentices in failed firms in Austria. When a firm fails, current apprentices cannot complete their training in this firm. Because apprentices will be at different stages in their apprenticeship, the failure of a firm will manipulate the length of the apprenticeship period completed for some apprentices. The time to failure therefore serves as an instrument for the length of the apprenticeship completed both at the original firm and at other firms. We find instrumental variables returns which are similar or larger than the OLS returns in our sample, indicating relatively little selection.
Keywords: 330; Human capital; returns to schooling; firm-based training; ability bias; Betriebliche Berufsausbildung; Bildungsertrag; Bildungsniveau; Humankapital; Schätzung; Österreich